The Prevalence of Myopia and its Associated Factors Among School-Aged Children in Pamijahan Village, Bogor District - Julie Dewi Barliana; Yeni Dwi Lestari; Ghina Fedora; Laura Agnestasia Djunaedi; Anthea Casey; Tri Rahayu; Ratna Sitompul; Andi Arus Victor; Saleha Sungkar (eJournal Kedokteran Indonesia, 2023)
Globaly, the prevalence of refractive errors, especially myopia in children, has increased significantly. The cause of myopia is multifactorial. Near-work activities and family history are some suggested factors associated with myopia. However, there has not been enough data on these factors and their association with myopia in Indonesia. This study aims to determine the prevalence and factors associated with myopia in primary and middle schoolaged children in Pamijahan Village, Bogor District, West Java, Indonesia. Data were taken in a cross-sectional design based on the visual acuity, anterior and posterior eye examination. A 14-item questionnaire regarding myopia-associated factors including family history, playing outdoors, and near-work activities, was distributed to the subjects. The data were taken from June to September 2018. Analysis was conducted using SPSS version 20. The prevalence of myopia in Pamijahan Village is 4,9% out of 474 subjects. Family history, including parental (p=0.001, OR 4.49) and sibling history (p=0.001, OR 5.58), was shown to be associated with the increasing risk of myopia in children while near-work activities and playing outdoors were not associated with myopia in children of Pamijahan Village.